Kajian Pendekatan Arsitektur Hijau pada Terminal Intermoda Joyoboyo - Wahyuno, M.Hafizh; Winarto, Erwin Djuni (Universitas Medan Area, 2025)
Transportation is an attempt to move people and goods from one place to another. The development of transportation in Indonesia itself is quite good, the various modes of transportation that exist must be accompanied by adequate facilities such as bus terminals. The bus terminal as a control center for bus vehicles certainly requires a large amount of energy to operate. Coupled with the large number of vehicles, the bus terminal has a fairly high air pollution rate. To overcome this problem can be done by implementing green architecture in designing bus terminals. By applying the principles of green architecture according to Brenda and Robert Vale, the problem of energy and air pollution at the terminal can be overcome. One of the terminals that has implemented green architecture is the Joyoboyo Terminal in Surabaya. The purpose of this research is to analyze existing green architecture principles to determine the effectiveness of green architecture in overcoming energy efficiency and air pollution problems at the terminal. Using a descriptive qualitative research method, it was found that the Joyoboyo Terminal building has implemented and integrated the six principles of green architecture according to Brenda and Robert Vale into the building design properly. These six principles alone are able to overcome problems of energy efficiency and air pollution very well so as to provide comfort to building users.